Rethinking the map of the political economy of communication and culture in the context of technological changes Era - Zaragoza Ramírez, Mario Alberto (2023)
Rethinking the theoretical map of the political economy of communication and culture is a pressing task in times where technological changes make visible new ways of understanding cultural consumption, inequality and the significant appropriation of contents. It is not only about information and knowledge technologies, or social media and streaming musical and audiovisual content. The approach and objective of mapping Political Economy, is to include new theoretical frontiers to think new challenges and methodological dimensions that put consumers at the center not only as a buyer or identities imitator, but as an enabler of differences crossed by technology, pollution and excessive consumption in a context of global economies. This contributes to expanding the discussion about the space-time relationship of emerging political, social and cultural processes in the public space.